2014
DOI: 10.1080/09670262.2014.977962
|View full text |Cite
|
Sign up to set email alerts
|

Combined effect of temperature and bleaching herbicides on photosynthesis, pigment and fatty acid composition ofChlamydomonas reinhardtii

Abstract: Norflurazon (Nf) and fluridone (Fd) are phytoene desaturase inhibitor herbicides that are widely used for the control of grasses and invasive aquatic weeds, respectively. These herbicides enter aquatic environments where they can negatively affect non-target plant species (e.g. algae). Their toxicity towards algae may be modified by abiotic factors such as light intensity, temperature, pH and nutrients. Investigating the effect of low temperature on the toxicity of Nf and Fd is particularly important because b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 49 publications
(45 reference statements)
3
20
0
Order By: Relevance
“…Several studies have examined the effects of climatic factors (such as temperature and irradiance) on photosynthesis of aquatic organisms (Huner et al, 2003;Necchi Jr, 2004). Temperature, for example, has been observed to modulate algal and cyanobacterial photosynthesis by modifying pigment and lipid compositions (and thus membrane fluidity) and enzyme activities (Huner et al, 2003;Necchi Jr, 2004;Chalifour et al, 2014). Although photoacclimation processes allow aquatic organisms to adjust their photosynthetic apparatus in response to changing light environments, prolonged exposure to high light intensities can induce photoinhibition and photodamage (Huner et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have examined the effects of climatic factors (such as temperature and irradiance) on photosynthesis of aquatic organisms (Huner et al, 2003;Necchi Jr, 2004). Temperature, for example, has been observed to modulate algal and cyanobacterial photosynthesis by modifying pigment and lipid compositions (and thus membrane fluidity) and enzyme activities (Huner et al, 2003;Necchi Jr, 2004;Chalifour et al, 2014). Although photoacclimation processes allow aquatic organisms to adjust their photosynthetic apparatus in response to changing light environments, prolonged exposure to high light intensities can induce photoinhibition and photodamage (Huner et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…A study into the inhibitory effects of fluridone on E. coli expressed PDS from the cyanobacterium Synechococcus (PCC 7492), as well as purified Synechococcus PDS, revealed a concentration of 0.3 μM and 3.5 μM to cause 50% inhibition of carotenoid production, respectively [38]. Chalifour, et al discovered that a range of temperatures influences the inhibitory effects of the herbicides norflurazon and fluridone in the model alga C. reinhardtii [35]. It was found that 1.25 μM fluridone had the greatest impact on secondary carotenoid formation at a temperature of 25 °C; whereas, secondary carotenoid formation was affected to a lesser extent at lower temperatures [35].…”
Section: Discussionmentioning
confidence: 99%
“…These bleaching herbicides target the enzyme phytoene desaturase (PDS), responsible for the downstream production of carotenoids past the metabolic step of phytoene production [34]. The inability to synthesize carotenoids that are essential for structure and function of photosynthetic complexes results in chlorophyll degradation, and ultimately, plant cell death [10,35,36,37]. At non-lethal doses, effective inhibition of PDS leads to the over-accumulation of phytoene [23,29,31,32,35,38].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“….06.347 et al 2014. For instance, an increase of MUFA and a decrease of PUFA and HUFA content were found on the green algae Scenedesmus and Chlamydomonas reinhardtii after respectively chloroacetamide treatment; norflurazon and fluridone exposure (Böger et al 2000, Chalifour et al 2014.…”
Section: Several Monitoring Tools Based On Diatom Community Compositimentioning
confidence: 99%